Research Progress of Carbon Fiber Composite Materials in Automobile Body Lightweight - Tang Haifeng (MATEC Web of Conferences)
Carbon fiber reinforced polymer (CFRP) has become a research hotspot in the field of automotive lightweight due to its high specific strength, low density and excellent energy absorption characteristics. Driven by the global “dual carbon” goal, vehicle lightweight has become the core path to reduce energy consumption and carbon emissions. In recent years, high-end models at home and abroad have achieved significant weight reduction through innovative design, while improving crash safety and endurance performance. However, the large-scale application of CFRP still faces challenges such as high raw material cost, insufficient process stability and recovery bottlenecks. The existing recycling technology has the risk of fiber performance loss or environmental protection, which restricts its sustainable development. In the future, it is necessary to optimize the production process through the research and development of new materials, intelligent manufacturing technology, and promote multi-material collaborative design to balance lightweight and cost control. This paper systematically reviews the technical progress, application cases and future challenges of CFRP in automotive lightweighting, and provides theoretical reference and practical direction for the green transformation of the industry.